PEMANFAATAN ARANG BRIKET LIMBAH TONGKOL JAGUNG SEBAGAI BAHAN BAKAR ALTERNATIF - Lukum, Haris; Isa, Ishak; Sihaloho, Mangara (Sainstek, 2012)
This study aims to utilize corn cob charcoal made briketdengan using sago pereket used variation in the ratio between sago and charcoal are: 1:3, 1:4, 2:3, 2:5. charcoal briquettes are made of corn cobs proksimasi testing include: air.kadar ash content, volatile compounds decomposition levels, the levels of heat, carbon-bound, and test the density of briquettes. comparing the corn cob charcoal briquettes with briquette quality standards through test proksimasi. test results of corn cob charcoal briquettes proksimasi dalah as follows: the level of water in 1:3 variation was 6.66%.,, 1:4 is 7.30%., 2:3 is 8.66%., 2:5 is 7.50%., 1:3 variation in ash content was 3.28%., 1:4 is 3.11%., 2:3 and 2:5 were 3.50% is 3.40%., Dekomposi volatile compounds in variations of 1:3 is 44.58., 1:4 is 58.99%., 2:3 is 2:5 adalah51 62.02%, 30%. Carbon bound to the variation of 1:3 is 45.48%., 1:4 is 54.56., 2:3 and 2:5 is 25.84 is 41.20. Calorific value of the variation of 1:3 is 6757kal / g. 1:4 is 6150kal / g., 2:3 is 3758 cal / g and 2:5 is 2912 cal / g.Kerapatan at 1:3 variation is 0.63 g/cm3., 1:4 is 0.60 g / cm3.,., 2:3 is 0.56 cal / g and 2:5 is 0.55 cal / g. Corn cob briquettes charcoal briquettes meet the quality standards by having a calorific value and high decomposition of volatile compounds that corn cob briquettes are of good quality